Using a "systems therapeutic for physiological renormalization" approach to vaccine development. Covid-19 as an example - Greg Maguire (Taylor & Francis Group, 2022)
Current vaccines for Covid-19 have failed to prevent the disease from spreading and have allowed more transmissible and virulent variants to form through mutations and recombinations as they replicate during the massive spread of the virions. Here I suggest using a "systems therapeutic" vaccine and dosing strategy to induce "physiological renormalization" to induce mimicry in the innate and adaptive immune systems in the respiratory tracts and sera, similar to that when the body encounters the natural infectious agent.